Practical analysis of using PPPH and raPPPid for Precise Point Positioning in Europe - Saber Mohamed; El-Mewafi Mahmoud; Awad Ahmed (Reports on Geodesy and Geoinformatics)
Assessing the reliability of using open-source software packages for post-processing of the Global Navigation Satellite System (GNSS) is essential since GNSS modernization has the potential to assist satellite navigation users. The purpose of this study is to evaluate the accuracy of using two MATLAB-based programs, raPPPid and PPPH for precise point positioning in Europe. Data from 12 MGEX stations over two days were used, with one day dedicated to each of the 6 stations and a 30-second observation interval. The data were post processed by PPPH and raPPPid programs and a comparison was made to evaluate the results accuracy produced by each software and the ones acquired from MGEX stations. Convergence time was also estimated. By comparing the root mean square error (RMSE) values for North, East and Up directions estimated by PPPH and raPPPid, it was found that raPPPid gives more accurate results where the RMSE in N direction estimated by raPPPid varied from 0.5 cm to 1.9 cm; however, RMSE in N direction estimated by PPPH varied from 0.7 cm to 2.8 cm. RMSE in E direction estimated by raPPPid varied from 0.4 cm to 3.3 cm, but RMSE in E direction estimated by PPPH varied from 0.5 cm to 3.7 cm. RMSE in Up direction estimated by raPPPid varied from 0.8 cm to 5.2 cm, while RMSE in Up direction estimated by PPPH varied from 0.9 cm to 5.5 cm. 3D Positioning error was also estimated by both software and it was found that the 3D positioning error estimated by raPPPid varied from 0.2 cm to 2.2 cm, whereas the 3D positioning error estimated by PPPH varied from 0.9 cm to 4.1 cm. Finally, the average convergence time achieved by raPPPid was 16.5 minutes, while the average convergence time achieved by PPPH was 32 minutes.